Development of E-Masl Learning Media Based on Multimodus Representation Oriented to Ethno-Stem - Suleta, Sri Devi; Simbolon, Merta; Palittin, Ivylentine D. (Journal of Innovative Physics Education Research, 2025)
This study aims to describe the results of the development of E-MASL (Electronic Malind Science Learning) Learning Media based on multimodus representation oriented Ethno-STEM which is made in the form of animated videos. E-MASL learning media discusses the concept of science learning in the culture of the Malind tribe in the process of burning stones to make sago sep, which is related to science learning materials, namely heat and its transfer. This type of research is Research and Development (R&D) research and uses a 4D (four-D) development model. The results of this study indicate that the average score of the validators is 83.33% with the category of "Very Eligible". The results of the student response questionnaire were 92.62% with the category of "Very Eligible". Therefore, it can be concluded that the development of E-MASL learning media based on multimodal representation oriented to Ethno-STEM has been tested and is feasible to be tested, so that the products of this study can be used as science learning media.